2022
DOI: 10.1021/acsami.2c02174
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the Impact of Diverse Morphology of Ionic Porous Organic Polymers with Mechanistic Insight on the Ultrafast and Selective Removal of Toxic Pollutants from Water

Abstract: In recent years, detoxification of contaminated water by different types of materials has received a great deal of attention. However, lack of methodical in-depth understanding of the role of various physical properties of such materials toward improved sorption performance limits their applicable efficiencies. In perspective, decontamination of oxoanion-polluted water by porous materials with different morphologies are unexplored due to a shortfall of proper synthetic strategies. Herein, systematic optimizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 43 publications
(73 reference statements)
0
20
0
Order By: Relevance
“…34,35 A judicious choice of monomers yields POPs in high yield via facile reactions that include but are not limited to metal catalyzed cross-coupling and condensation polymerization. [36][37][38][39][40] Among the various methodologies, Schiff base condensation is a very simple and efficient reaction to synthesize imine linked POPs that have wide applications in the elds of gas storage, catalysis, biology, energy, environmental remediation and so on. [41][42][43] A literature survey indicated that only a few imine-linked POPs have been explored to date as strategic materials for iodine capture and storage purpose.…”
Section: Introductionmentioning
confidence: 99%
“…34,35 A judicious choice of monomers yields POPs in high yield via facile reactions that include but are not limited to metal catalyzed cross-coupling and condensation polymerization. [36][37][38][39][40] Among the various methodologies, Schiff base condensation is a very simple and efficient reaction to synthesize imine linked POPs that have wide applications in the elds of gas storage, catalysis, biology, energy, environmental remediation and so on. [41][42][43] A literature survey indicated that only a few imine-linked POPs have been explored to date as strategic materials for iodine capture and storage purpose.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the luminescent porous material based fluorescence technique for the detection of target-specific environmental contaminants has received special research attention, owing to its pre-concentration effect, high sensitivity, selectivity, reusability, low fabrication and operational costs, etc. Compared to traditional porous materials, such as activated carbon, zeolites, and resin, advanced porous materials such as metal–organic frameworks (MOFs) and porous organic polymers (POPs) have recently been shown to be promising toward sensing application because of their improved sensitivity, high selectivity, and fast response. , Although several MOF-based antibiotic and pesticide sensing studies have been reported, , the detection of these species with low-cost and thermally and chemically stable highly luminescent POPs is very rarely explored. , POPs are a class of porous materials constructed with strong covalent bonds between various pure organic building blocks as a potential scaffold, featuring highly tunable porosity and excellent chemical and thermal stability. The successful development of such materials with the aforementioned properties along with rational incorporation of fluorophores also offers advantages toward construction of efficient sensory materials. The high porosity and large surface area of these materials allow fast mass diffusion and strong interaction of the probes with the targeted analytes and thus further result in rapid detection and sensitivity, respectively. Moreover, the heterogeneous nature coupled with high chemical stability of these materials enables the easy and superior recyclable detection ability of these probes, making them useful for different environments. , …”
Section: Introductionmentioning
confidence: 99%
“…However, the rapid industrialization in recent times, to satiate the demands of the inflating population, has led to significant exploitation of this crucial natural resource. Therefore, the remediation of contaminated water has attracted worldwide attention . Scientific research indicates that anthropogenic water pollutants consist of organic as well as inorganic chemical species that are released into the environment owing to human activity. These pollutants comprise various species that include but are not limited to pharmaceutical products, herbicides/pesticides, organic dyes, toxic metal ions, and radioactive species, which find their way into the ecosystem. …”
Section: Introductionmentioning
confidence: 99%